Distributed Functional Connectome of White Matter in Patients With Functional Dyspepsia - Xu, Qiang; Weng, Yifei; Liu, Chang; Qiu, Lianli; Yang, Yulin; Zhou, Yifei; Wang, Fangyu; Lu, Guangming; Zhang, Long Jiang; Qi, Rongfeng (Frontiers in Human Neuroscience, 2021)
Purpose: We aimed to find out the distributed functional connectome of white matter in patients with functional dyspepsia (FD). Methods: 20 patients with FD and 24 age- and gender-matched healthy controls were included into the study. The functional connectome of white matter and graph theory were used to these participants. Two-sample t-test was used for the detection the abnormal graph properties in FD. Pearson correlation was used for the relationship between properties and the clinical and neuropshychological information. Results: Patients with FD and healthy controls showed small-world properties in functional connectome of white matter. Compared with healthy controls, the FD group showed decreased global properties (Cp, S, Eglobal, and Elocal). Four pairs of fiber bundles that are connected to the frontal lobe, insula, and thalamus were affected in the FD group. Duration and Pittsburgh Sleep Quality Index positively correlated with the betweenness centrality of white matter regions of interest. Conclusion: FD patients turned to a non-optimized functional organization of WM brain network. Frontal lobe, insula, and thalamus were key regions in brain information exchange of FD. It provided some novel imaging evidences for the mechanism of FD.